INFLUENT ENELBIN ON NEUROHYMORAL HOMEOSTASIS AT DYSCIRCULATION ENCEPHALOPATHY CAUSED BY HYPERTONIC ILLNESS - КapustinR.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
During research it was established, that the enelbin (naftidrofuril) normalized parameters neurohymoral homeostasis at patients with chronic infringements of brain blood circulation. The preparation the enelbin is a medical product of a choice in treatment dyscirculation encephalopathy.